The adverse impact of riba on individual and society: a concise and comprehensive study - Ahmed Rufai (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2014)
There is no difference of opinion among Muslims that Riba i.e. interest or usury is Haram i.e. unlawful under the Shari’ ah i.e. Islamic Law principles. This has been confirmed in the Holy Qur’an, in the Sunnah i.e. tradition of Prophet Muhammad (S.A.W.) and the Muslims consensus agreement since the early stage of Islam until today. The aim of this article is to explain why Islam has prohibited business and transactions that involve Riba and how Muslims are urged by Islam to engage in business and trade which are ethical in nature and character. The Arabic word Riba linguistically means increase and growth. It means increase in anything, or addition to anything. In other words, increase in capital at the expense of the wealth of others through means which are false and wrong. Hence, any addition however slight, over and above the principal sum lent that is, Riba. This evil activity i.e. Riba, no doubt creates selfishness, money-worship, cruelty, hard-heartedness and kills the spirit of fellow feeling and co-operation, it is therefore, ruinous for society spiritually, morally and economically. Islam has prohibited Riba in order to protect the property of the Muslims and not to be eaten unjustly, to encourage and direct Muslims to invest their money through Halal i.e. lawful channels and block anything that will generate hatred, evil and envy among the Muslims. Because if Riba is made permissible the needy person will be required to pay back more on loans and from the moral aspect this will weaken his feelings of good will and friendliness toward the lender. Hence, if Riba is prohibited in a society, people will lend to each other with goodwill, expecting back no more than what they have loaned, so that the spirit of mercy and charity among Muslims will be more firm and strong.